PEMBUATAN ABON DARI JANTUNG PISANG (MUSA PARADISIACA) DENGAN PENAMBAHAN IKAN TONGKOL (EUTHYNNUS AFFINIS) - Jusniati Jusniati; Patang Patang; Kadirman Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
This research aims to determine the influence addition mackarel tuna on organoleptic quality and chemical characteristic of the best banana blossom's abon. The research used completely randomized design method.  Parameter that was observed consist of water content,  protein,  fat,  carbohydrate,  crude fibers and organoleptic consist of taste,  colour,  aroma anf texture.  Analysis data using variety analysis. The result of the research was show that banana blossom's abon that really like of panelists is the banana blossom's abon that resulting on A treatment by comparison 50% of the banana blossom anf 50% of the mackarel tuna.